2016
DOI: 10.1021/acs.jpcc.5b10129
|View full text |Cite
|
Sign up to set email alerts
|

Probing Interconnectivity in Hierarchical Microporous/Mesoporous Materials Using Adsorption and Nuclear Magnetic Resonance Diffusion

Abstract: Adsorption and transport in hierarchical materials are investigated by means of adsorption and nuclear magnetic resonance experiments. Using micro/mesoporous zeolites with well-defined mesoporosity, we show that adsorption at a given pressure can be described as a simple linear combination of the adsorbed amounts taken at the same pressure for the pure microporous (zeolite FAU-Y) and mesoporous (Al-MCM-41) solids. Such a quantitative decomposition allows us to demonstrate the ability of diffusion measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 38 publications
2
82
0
Order By: Relevance
“…22 Different experimental conditions have been reported in the literature for the synthesis of FAUmes starting from zeolite crystals with various Si/Al ratios, using several sources of alkali (NaOH, TMAOH, NH 4 OH), different temperatures (80, 115, 150 °C), different durations (12 to 24 h) and different types and amounts of alkyltrimethylammonium surfactants (CnTAX, n = 10 -22, X = Cl, Br). 4,[14][15][16][17][18][19][20][21][22][23][24] In the present study, a systematic investigation of the materials resulting from the transformation of FAU-Y (Si/Al = 15) into FAUmes has been performed. Materials have been prepared using C18TAB as surfactant and NaOH as the alkali from mixtures with molar ratios 1 SiO 2 / n NaOH / 0.1 C18TAB / H O (n = 0.025 -0.25) at 115 °C for h. Our aim was to analyze precisely their structural, textural and acidic properties as a function of NaOH/Si ratio.…”
Section: Introductionmentioning
confidence: 99%
“…22 Different experimental conditions have been reported in the literature for the synthesis of FAUmes starting from zeolite crystals with various Si/Al ratios, using several sources of alkali (NaOH, TMAOH, NH 4 OH), different temperatures (80, 115, 150 °C), different durations (12 to 24 h) and different types and amounts of alkyltrimethylammonium surfactants (CnTAX, n = 10 -22, X = Cl, Br). 4,[14][15][16][17][18][19][20][21][22][23][24] In the present study, a systematic investigation of the materials resulting from the transformation of FAU-Y (Si/Al = 15) into FAUmes has been performed. Materials have been prepared using C18TAB as surfactant and NaOH as the alkali from mixtures with molar ratios 1 SiO 2 / n NaOH / 0.1 C18TAB / H O (n = 0.025 -0.25) at 115 °C for h. Our aim was to analyze precisely their structural, textural and acidic properties as a function of NaOH/Si ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Thus, much effort has been made to study such idealizedsystems. [8][9][10][11] It is true that recent progress in PFG NMR methodology [12] has facilitated diffusion studies in also more complex pore architectures [13][14][15][16] just as the investigationof highly heterogeneouss ystemsb eing characterized by ad istribution of diffusivities. [16,17] However,a pplication of such advanced techniques requires high accuracyi nt he spinecho attenuations, which cannotb ee xpectedt ob ea ttainable as ar ule.…”
mentioning
confidence: 99%
“…Although these values were attributed to intercrystalline diffusion of toluene molecules for the non-modified ZSM5-nano sample, the data indicate that it is not the case for the desilicated sample. This effect was shown by Coasne et al [53] when analyzing the effective diffusivity of nhexane in hierarchical FAU. However, for ZSM5-meso, the observed diffusion behavior remains at a higher value than the microporous samples which may imply that the molecules of toluene diffuse merely within the crystals.…”
Section: Industrial Catalystsmentioning
confidence: 53%
“…As the structure possesses larger pores ( Figure S4), the diffusion becomes faster. This effect was shown by Coasne et al [53] when analyzing the effective diffusivity of nhexane in hierarchical FAU. These authors showed that a zeolite possessing both micro-and mesopores exhibits a diffusion value intermediate between the diffusion in purely microporous structure and purely mesoporous MCM-41.…”
Section: Industrial Catalystsmentioning
confidence: 53%